Temperature sensing by the calcium-sensing receptor - Brennan, Sarah C.; Mun, Hee-chang; Delbridge, Leigh; Kuchel, Philip W.; Conigrave, Arthur D. (Frontiers in Physiology, 2023)
Whether GPCRs support the sensing of temperature as well as other chemical and physical modalities is not well understood. Introduction: Extracellular Ca2+ concentration (Ca2+o) modulates core body temperature and the firing rates of temperature-sensitive CNS neurons, and hypocalcemia provokes childhood seizures. However, it is not known whether these phenomena are mediated by Ca2+o-sensing GPCRs, including the calcium-sensing receptor (CaSR). In favor of the hypothesis, CaSRs are expressed in hypothalamic regions that support core temperature regulation, and autosomal dominant hypocalcemia, due to CaSR activating mutations, is associated with childhood seizures. Methods: Herein, we tested whether CaSR-dependent signaling is temperature sensitive using an established model system, CaSR-expressing HEK-293 cells. Results: We found that the frequency of Ca2+o-induced Ca2+i oscillations but not the integrated response was linearly dependent on temperature in a pathophysiologically relevant range. Chimeric receptor analysis showed that the receptor’s C-terminus is required for temperature-dependent modulation and experiments with the PKC inhibitor GF109203X and CaSR mutants T888A and T888M, which eliminate a key phosphorylation site, demonstrated the importance of repetitive phosphorylation and dephosphorylation. Discussion and Conclusion: CaSRs mediate temperature-sensing and the mechanism, dependent upon repetitive phosphorylation and dephosphorylation, suggests that GPCRs more generally contribute to temperature-sensing.